2013
DOI: 10.4067/s0717-95022013000400039
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Parameters of the Left Coronary Artery: an Angiographic Study in a South African Population

Abstract: SUMMARY: An understanding of the left coronary artery (LCA) anatomy is important for accurate diagnosis and therapeutic intervention in the management of coronary arterial diseases. This angiographic study aims to document the parameters of the LCA that may be of importance in the diagnosis and treatment of coronary artery diseases. An analysis of 151 coronary angiograms obtained from the cardiac catheterization laboratory in the eThekwini Municipality area of KwaZulu-Natal, South Africa was performed. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Quadrifurcation of the LCA (Type C) was recorded in 2.4 % of the specimens and was similar to the reports of Ajayi et al (2013) (0.7 %), Santhoshkumar et al (2 %) and Jaishree et al (4 %). The incidence of Type C was however lower than that of Kalpana, Ogeng'o et al and Beg et al, and who recorded 11 %, 9.6 % and 10 %, respectively (Table III).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Quadrifurcation of the LCA (Type C) was recorded in 2.4 % of the specimens and was similar to the reports of Ajayi et al (2013) (0.7 %), Santhoshkumar et al (2 %) and Jaishree et al (4 %). The incidence of Type C was however lower than that of Kalpana, Ogeng'o et al and Beg et al, and who recorded 11 %, 9.6 % and 10 %, respectively (Table III).…”
Section: Discussionsupporting
confidence: 78%
“…LCA Type B (trifurcation), occurred in 29.3 % and was similar to Dattatray et al (35.9 %), Ajayi et al (2013) (18.5 %), Tomar et al (24 %),Ogeng'o et al (32.2 %) and Santhoshkumar et al (26 %). This differed from the results of Kulkarni & Mehta (2012) and Jaishree et al (2015) who found 11.54 % and 14.5 %, respectively (Table III).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These findings suggest ethnic variability and appear to support the suggestion by Garg et al (2000) in some individuals. About 10 % of clinical malpractice is due to the ignorance of the anatomical variations (Ajayi et al, 2013). The size of the coronary arteries typically determines the treatment options in the management of coronary artery disease as small arteries may cause anastomotic difficulties during bypass grafting and can influence the outcome in procedures such as stenting and balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%